2017
DOI: 10.1002/ange.201700282
|View full text |Cite
|
Sign up to set email alerts
|

Partial Reduction and Selective Transfer of Hydrogen Chloride on Catalytic Gold Nanoparticles

Abstract: HCl in solution accepts electron density from Au NPs and partially reduces at room temperature, as occurs with other simple diatomic molecules, such as O2 and H2. The activation can be run catalytically in the presence of alkynes to give exclusively E‐vinyl chlorides, after the regio‐ and stereoselective transfer of HCl. Based also on this method, vinyl chloride monomer (VCM) can be produced in a milder and greener way than current industrial processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…In a recent work from our group, a different reaction mechanism is proposed for hydrochlorination of alkynes on Au nanoparticles when working in the liquid phase. 542 Metallic Au nanoparticles supported on TiO 2 are proved to be the most active catalyst for hydrochlorination of phenylacetylene, while mononuclear Au complexes or subnanometric Au clusters are not active under the same conditions. According to the results presented, the activation of HCl is found to be the rate-limiting step, and its activation is more favorable on metallic Au surface.…”
Section: Comparison Of the Catalytic Behavior Of Single Atoms Nanoclmentioning
confidence: 99%
“…In a recent work from our group, a different reaction mechanism is proposed for hydrochlorination of alkynes on Au nanoparticles when working in the liquid phase. 542 Metallic Au nanoparticles supported on TiO 2 are proved to be the most active catalyst for hydrochlorination of phenylacetylene, while mononuclear Au complexes or subnanometric Au clusters are not active under the same conditions. According to the results presented, the activation of HCl is found to be the rate-limiting step, and its activation is more favorable on metallic Au surface.…”
Section: Comparison Of the Catalytic Behavior Of Single Atoms Nanoclmentioning
confidence: 99%
“…The process is a textbook example of sacrificing environment for societal progress, due to the massive demand of polyvinyl chloride (PVC, > USD 45 billion market) in a number of sectors, mostly in building and construction. [23][24][25][26][27][28] At present, the monomer vinyl chloride (VCM) is produced from ethylene (ca. 65%) or acetylene (ca.…”
mentioning
confidence: 99%
“…A previous work by Corma et al demonstrated that Au NPs were a highly efficient catalyst for the nucleophilic addition of HCl to terminal alkynes. 56 Therefore, this reaction was selected as a model reaction here due to the involvement of high HCl concentration which highlights the necessity to use an acid stable catalyst. We aim to study whether the hollow MOF-801 shell can enable size selective catalyst between a small alkyne, 4-ethynyltoluene (EL), and a bulky alkyne, 1-ethynylnaphthalene (EN).…”
Section: Resultsmentioning
confidence: 99%